Pendampingan Masyarakat dalam Mengakses dan Memahami Hak Hak Politik - Fransin Kontu; Umiyati Haris; Imelda C. Laode; Hubertus Oja; Samuel Atbar (Universitas 17 Agustus 1945 Semarang, 2024)
This community service activity aims to increase people's understanding of and access to their political rights. The main focus of this program is to provide assistance and education to the community about the importance of political participation and ways to access political rights effectively. Through a series of activities such as education, group discussions, and individual consultation sessions, this program is expected to empower the community to be more actively involved in the democratic process. The results of this activity show a significant increase in community knowledge and skills in understanding community political rights, as well as increased participation in local political activities. The program was also successful in creating a support network among participants that can continue to serve as a source of information and assistance in the future. Thus, this service contributes to strengthening the community's capacity to actively participate in inclusive and sustainable political development.